2009
DOI: 10.1108/01437720910956772
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of knowledge management on social interaction and innovation performance

Abstract: Purpose -The purpose of this paper is to examine the mediating role of knowledge management in the relationship between social interaction and innovation performance. Design/methodology/approach -The population in the study is the Taiwanese firms listed in the China Credit Information Service Incorporation. A stratified random sampling method was used to select 176 firms in Taiwan. The usable response rate was 23.47 per cent. The study employed LISREL to test the hypothesized relationships in the path-analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
136
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(162 citation statements)
references
References 60 publications
(206 reference statements)
10
136
0
4
Order By: Relevance
“…By activating IT integration with a small number of external knowledge providers repeatedly, firms closely interact with their partners. This may increase inter-organizational cohesion and mutual support, and cultivate a benign environment for radical innovations (Huang and Li 2009;López-Cabrales et al 2008). M a n u s c r i p t…”
Section: It Integration and External Search Depthmentioning
confidence: 99%
“…By activating IT integration with a small number of external knowledge providers repeatedly, firms closely interact with their partners. This may increase inter-organizational cohesion and mutual support, and cultivate a benign environment for radical innovations (Huang and Li 2009;López-Cabrales et al 2008). M a n u s c r i p t…”
Section: It Integration and External Search Depthmentioning
confidence: 99%
“…Accordingly, IOT can influence innovative activity through many mechanisms, such as the reduction of the need for formal monitoring and bargaining over agreement (Tamaschke, 2003), valuable knowledge sharing (Inkpen & Tsang, 2005), and less risk averse encouraging investors to invest more in R&D projects (Akçomak & ter Weel, 2006). Different studies have suggested that the closeness or connectivity of social relationship between two parties allows firms to benefit from knowledge distributed and accumulated by close contacts and interactions, thereby, to further achieve favorable innovation (Huang et al, 2009). For instance, Dyer and Nobeoka (2000) demonstrated Toyota and its suppliers' highly interconnected networks which create a strong coordinating rules motivate members to openly share valuable knowledge and engage in multidirectional knowledge flows and innovation.…”
Section: Relational Capital: Iot and Comentioning
confidence: 99%
“…For example, a plethora of studies have revealed the significant influence of trust towards knowledge sharing [20]. Cook and Wall (1980, p. 39) defined trust as "the extent to which one is willing to ascribe good intentions to and have confidence in the words and actions of other people" [21].…”
Section: Literature Reviewmentioning
confidence: 99%